2015
DOI: 10.1007/s12035-015-9370-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Common Variations in PLD3 on Neuroimaging Phenotypes in Non-demented Elders

Abstract: Rare variants of phospholipase D3 (PLD3) have been identified as Alzheimer's disease (AD) susceptibility loci, whereas little is known about the potential role of common variants in the progression of AD. To examine the impact of genetic variations in PLD3 on neuroimaging phenotypes in a large non-demented population. A total of 261 normal cognition (NC) and 456 mild cognitive impairment (MCI) individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database are included in our analysis. Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Rare variants of PLD3 are confirmed AD susceptibility loci; phospholipase D3 modulates APP processing. However, a common variant in the same gene, rs10407447, was associated with regional metabolism and lateral ventricular volume in CN and MCI subjects [190]. A study of SNPs found in genes preferentially expressed in the hippocampus identified a novel locus, NAV2 (neuron navigator 2), associated with episodic memory scores [191].…”
Section: Studies Of Genetic Associationsmentioning
confidence: 99%
“…Rare variants of PLD3 are confirmed AD susceptibility loci; phospholipase D3 modulates APP processing. However, a common variant in the same gene, rs10407447, was associated with regional metabolism and lateral ventricular volume in CN and MCI subjects [190]. A study of SNPs found in genes preferentially expressed in the hippocampus identified a novel locus, NAV2 (neuron navigator 2), associated with episodic memory scores [191].…”
Section: Studies Of Genetic Associationsmentioning
confidence: 99%
“…Several variations in the PLD3 gene increase the risk to develop late-onset Alzheimer's disease (LOAD), and particularly one variant (Val232Met) doubles the risk of developing the disease (Cruchaga et al, 2014). However, more recent studies reproduced the association only in part or did not even find an association at all (Heilmann et al, 2015;Hooli et al, 2015;Lambert et al, 2015; van der Lee et al, 2015;Wang et al, 2015Wang et al, , 2016Zhang et al, 2016). Overexpression of PLD3 decreases the levels of both full-length APP and extracellular amyloid b (Ab) under conditions of high overexpression, whereas PLD3 knockdown increases extracellular Ab levels (Cruchaga et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PLD3 is expressed in pyramidal neurons within the brain, and in AD brains, PLD3 co-localizes with amyloid plaques [8, 9]. Common variants in PLD3 are associated with CSF Aβ levels, an AD biomarker [10]. In vitro , PLD3 expression is correlated with extracellular Aβ levels: Pld3 silencing is associated with increased Aβ levels, and PLD3 overexpression is associated with reduced Aβ levels [4].…”
Section: Introductionmentioning
confidence: 99%